Crashworthiness design and impact tests of aluminum foam-filled crash boxes. (November 2022) - Wang, Gaofei; Zhang, Yongliang; Zheng, Zhijun; Chen, Haibo; Yu, Jilin
Abstract: The optimization of foam-filled crash boxes is desired to enhance the energy-absorbing capacity of frontal crash management systems and improve vehicle crash safety. A novel foam-filled crash box with partial filling and combined trigger design is proposed based on a double tubular structure. Compression and impact simulations were performed to analyze the energy absorption capacity, initial peak force, deformation modes, and protection capability of the original and improved crash boxes. It is shown that the partial filling design can reduce 67% of the foam used and increase the specific energy absorption compared with the full-filling design. The triggers and the crash-box length together determine the stability of the subsequent deformation after initial buckling. An improved optimization design strategy for the foam-filled crash box is proposed by considering the material utilization and the deformation stability of the frontal system. The design strategy is validated by compression and trolley impact tests. Therefore, the optimization design method of the crash box, considering the joint action of key indicators, is appropriate and convenient for the crashworthiness design of crash boxes. Highlights: A partially foam-filled double-tube crash box with combined triggers is proposed. The proposed structure can significantly increase the specific energy absorption. The trigger and length are dominant to the deformation stability after initial buckling. An improved optimization design strategy for the foam-filled crash box is proposed. The optimized design of the crash box is verified by conducting trolley impact tests.